Cathode materials for ceramic based microbial fuel cells (MFCs). (9th November 2015) - Santoro, Carlo; Artyushkova, Kateryna; Gajda, Iwona; Babanova, Sofia; Serov, Alexey; Atanassov, Plamen; Greenman, John; Colombo, Alessandra; Trasatti, Stefano; Ieropoulos, Ioannis; Cristiani, Pierangela
Abstract: This study showed the electrochemical performance of different cathode electrodes tested on a ceramic separator functioning as a cation exchange membrane. Particularly, three different carbonaceous-based materials (carbon cloth (CC), carbon mesh (CM) and carbon veil (CV)) have been used as an electrode and as the current collector. When used as an electrode, CC outperformed the others. The carbonaceous materials have been modified using conductive paint (PA) and micro porous layer (MPL). With these modifications, the current output was two–three times higher. Generally, the current produced was slightly higher with MPL treatment compared to PA except in the case of CV-MPL that had lower output probably due to the negative effect of the heat treatment on the mechanical strength of the CV. In the case of PA, the current collectors do not seem to affect the output. The same consideration can also be done for the MPL except for the CV. The surface morphology seems to explain the results. Linear correlation was found between current produced and nanoscale roughness and skewness. The results indicated that those morphological parameters increased the contact between the cathode and the ceramic surface, thus enhancing the current generated. The further addition of the inorganic non-platinum group catalyst (Fe-AAPyr) on the surface significantly enhanced the performances. Following MPL modification and MPL-Fe-AAPyr addition, CM was the most cost effective support. CV was the most cost effective support with PA modification. Graphical abstract: Highlights: Ceramic separator filled with PBS was used during the electrochemical experiments. Carbon cloth, mesh and veil were used as cathode and current collector. Carbon cloth had higher performances despite the higher cost. Modification with conductive paint and powder enhanced the performances. The addition of Fe-AAPyr boosted the performances significantly.